Caracterização morfofisiológica e micropropagação de alcachofra - Costa, Angélica Reolon da (2011)
To encourage consumption of fresh artichokes in southern Brazil, it is important the selection and introduction of uniform genotypes with this purpose. This requires knowledge of the natural variability existing in the species and development of strategies to achieve high product uniformity. This study was conducted to evaluate the variability in a collection of artichoke, to select genotypes with fitness for fresh consumption and to establish a micropropagation protocol for cv. Nobre in order to provide subsidies for the improvement of artichoke in Brazil. Nineteen artichoke genotypes, including five commercial cultivars, fourteen non-commercial and forty accessions of cv. Round Enhanced Green were characterized based on morphological characteristics. For the study of micropropagation, two disinfectants agents were tested (sodium hypochlorite and gentamicin antibiotic) in isolation medium and five multiplication media. The explants for micropropagation were obtained from shoots of cv. Noble. It was observe the existence of genetic variability among genotypes, being the farther of Mahalanobis distance observed between Israel and a Romanesque (d =. 131.68.) and the lower distance between Round Green and Round Enhanced Green cvs. (d=1.40). Using cluster analysis, four groups were formed, distinguishing itself by: thickness of the fund, fresh mass of the fund / fresh weight of the capitulum ratio, diameter of the capitulum fund, length of the external bract, length of the primary capitulum, length of bracts base, plant height, plant diameter, capitulum diameter and thickness of the primary bracts. Group I accessions presented the best characteristics for fresh consumption. In relation to the phenotypic variability studied among the forty accessions of Round Enhanced Green cv. it was observed genetic dissimilarity among them, indicating the possibility of intravarietal selection in this cultivar. In relation to the in vitro culture experiments conduced with the Nobre artichoke cultivar, the sodium hypochlorite (NaClO) and the antibiotic gentamicin proved to be equally effective in controlling bacterial infections during the isolation. In the second subculture highest multiplication rates were observed on media M4 and M2 (4,57:1 and 4,00:1, respectively). In the third subculture, the highest rate of multiplication was observed in medium M2 (5,9:1), being superior to the others. The rooting frequency was 62%, and in the acclinatization phase, the percentage of survival was 44,83% and 37,93% at 30 and 60 days after transplantation, respectively. These results demonstrate the feasibility of commercial use of micropropagation for this Brazilian cultivar of artichoke